La renovación. Vestidos de la armadura de Jesucristo (2021)
From the autobiographical-narrative analysis, the renovation is analyzed as dresses of the armor of Jesus Christ; this is the complex objective of the investigation. To do this, we turn to the Sacred Scriptures as sustenance, together with subjectivity, in the experiences and experiences of the author in her journey as a human being that Christianity proposes; that is: the subjection to Jesus Christ as teacher, son of God and savior of the world. This inquiry is considered in the line of research entitled: transepistemologies of knowledge and transcomplex transmethodologies. Deeply intertwined rhizomes will run; while renewal is prone in areas such as: faith, mind, our holiness, our lifestyle and relationship with God.